2015
DOI: 10.2147/dddt.s92117
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacokinetics of dicloxacillin in healthy Chinese volunteers following single and multiple oral doses

Abstract: BackgroundDicloxacillin, a semisynthetic isoxazolyl penicillin antibiotic, has antimicrobial activity against a wide variety of gram-positive bacteria including Staphylococcus aureus, Streptococcus pyogenes, Streptococcus pneumonia, Streptococcus epidermidis, Streptococcus viridans, Streptococcus agalactiae, and Neisseria meningitidis. The objective of this study was to evaluate the safety and pharmacokinetic profile of dicloxacillin after single and multiple oral dose in healthy Chinese volunteers.MethodsA si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…Previous studies have proved that it showed time-dependent bactericidal activity and could be well tolerated in patients and volunteers 12,17. Several studies on PK properties of dicloxacillin revealed that it can be rapidly absorbed after oral administration, with the higher serum concentration, absolute bioavailability, and cumulative urinary excretion compared with other isoxazole penicillins, such as oxacillin and cloxacillin 18,19.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies have proved that it showed time-dependent bactericidal activity and could be well tolerated in patients and volunteers 12,17. Several studies on PK properties of dicloxacillin revealed that it can be rapidly absorbed after oral administration, with the higher serum concentration, absolute bioavailability, and cumulative urinary excretion compared with other isoxazole penicillins, such as oxacillin and cloxacillin 18,19.…”
Section: Discussionmentioning
confidence: 97%
“…Previous publication trial of dicloxacillin in healthy Chinese volunteers provides reference PK parameters for our Monte Carlo simulation 12. They found that C max and AUC 0–∞ were approximately four times and five times higher in healthy Chinese subjects compared with Western population 12,20.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations